Development of central nervous system metastases as a first site of metastatic disease in breast cancer patients treated in the neoadjuvant trials GeparQuinto and GeparSixto - Laakmann, Elena; Schneeweiss, Andreas (Breast cancer research, 2019)
Background: The incidence of central nervous system (CNS) metastases in breast cancer patients is rising and has become a major clinical challenge. Only few data are published concerning risk factors for the development of CNS metastases as a first site of metastatic disease in breast cancer patients. Moreover, the incidence of CNS metastases after modern neoadjuvant treatment is not clear. - Methods: We analyzed clinical factors associated with the occurrence of CNS metastases as the first site of metastatic disease in breast cancer patients after neoadjuvant treatment in the trials GeparQuinto and GeparSixto (n = 3160) where patients received targeted treatment in addition to taxane and anthracycline-based chemotherapy. - Results: After a median follow-up of 61 months, 108 (3%) of a total of 3160 patients developed CNS metastases as the first site of recurrence and 411 (13%) patients had metastatic disease outside the CNS. Thirty-six patients (1%) developed both CNS metastases and other distant metastases as the first site of metastatic disease. Regarding subtypes of the primary tumor, 1% of luminal A-like (11/954), 2% of luminal B-like (7/381), 4% of HER2-positive (34/809), and 6% of triple-negative patients (56/1008) developed CNS metastases as the first site of metastatic disease. In multivariate analysis, risk factors for the development of CNS metastases were larger tumor size (cT3-4; HR 1.63, 95% CI 1.08-2.46, p = 0.021), node-positive disease (HR 2.57, 95% CI 1.64-4.04, p < 0.001), no pCR after neoadjuvant chemotherapy (HR 2.29, 95% CI 1.32-3.97, p = 0.003), and HER2-positive (HR 3.80, 95% CI 1.89-7.64, p < 0.001) or triple-negative subtype (HR 6.38, 95% CI 3.28-12.44, p < 0.001). - Conclusions: Especially patients with HER2-positive and triple-negative tumors are at risk of developing CNS metastases despite effective systemic treatment. A better understanding of the underlying mechanisms is required in order to develop potential preventive strategies.